TRANSVERSE TESTICULAR ECTOPIA - Shamsuddin, Syed; Mirza, Tassawar Hussain; Khan, Naveedullah; Ibrahim, Muhammad; Imtiaz, Tashfeen (Journal of Ayub Medical College Abbottabad, 2007)
We present a case of Transverse testicular ectopia of the right testis that presented to our surgical out patient department with left inguinal hernia and an impalpable testis in the right scrotum. Patient was operated. Left herniotomy was performed and right testis was found in the left inguinal canal which was brought to the right scrotum and anchored through suprapubic subcutaneous tunnel. Key words : Transverse testicular ectopia, Inguinal hernia, Urogenital anomalies